Comprehensive transcriptome profiling in elderly cancer patients reveals aging‐altered immune cells and immune checkpoints. Issue 7 (12th December 2018) - Wu, Yingcheng; Wei, Jinhuan; Chen, Xia; Qin, Yongwei; Mao, Renfang; Song, Jian; Fan, Yihui
Abstract : Aging is the single most significant risk factor for cancer development. However, the potential impact of aging on cancer microenvironment remains poorly understood. Here, we performed a pan‐cancer transcriptome analysis to identify aging‐specific molecular patterns across 18 cancer types. Strikingly, aging‐specific molecular features define human cancers into two types, including the strong and weak aging‐effect groups. Significant aging associated molecular signature was observed in 16 cancer types (strong aging‐effect group) such as breast invasive carcinoma and acute myeloid leukemia. In such 16 cancer types, old patients showed obvious poor survival compared to young patients, but this observation was not found in the weak aging‐effect cancers. Aging‐associated cancer‐relevant molecules significantly enriched in 23 pathways including EMT and KRAS signaling. More interestingly, in cancer microenvironment, aging significantly restrains adaptive immunity, but strikingly, increases the number of infiltrated innate immune cells. Further analysis shows that the expression of immune checkpoints including PD‐1, PD‐L1, PD‐L2 and CTLA‐4 are mostly correlated with age. In general, cancer cells in elderly patients show a more aggressive phenotype and their surrounding microenvironment is under a more immune suppression status compared to young patients. Our study provides a systematic understanding of aging‐associated molecular features in pan‐cancer and indicates a clinical requirement to develop aging‐specific therapeutic strategies in a majority of cancer types. Furthermore, aging‐altered immune cells and immune checkpoints should be considered in cancer immunotherapy. Abstract : What's new? Simply getting older increases the chances of developing some form of cancer, but it is still unclear exactly why. Here, the authors sequenced transcriptomes from 18 cancer types, looking for gene expression differences between young and old patients that transcend tissue type. They found strong aging‐associated molecular changes in 16 cancer types, and in those cases, older patients had poor survival than the younger group. Older patients also had a distinctly different immune microenvironment, with higher levels of 11 immune checkpoints and reductions in adaptive immune cells. Older patients, then, may respond differently to immunotherapy.